Fucosterol Protects against Concanavalin A-Induced Acute Liver Injury: Focus on P38 MAPK/NF-κB Pathway Activity. (17th July 2018) - Mo, Wenhui; Wang, Chengfen; Li, Jingjing; Chen, Kan; Xia, Yujing; Li, Sainan; Xu, Ling; Lu, Xiya; Wang, Wenwen; Guo, Chuanyong
Abstract : Objective . Fucosterol is derived from the brown alga Eisenia bicyclis and has various biological activities, including antioxidant, anticancer, and antidiabetic properties. The aim of this study was to investigate the protective effects of fucosterol pretreatment on Concanavalin A- (ConA-) induced acute liver injury in mice, and to understand its molecular mechanisms. Materials and Methods . Acute liver injury was induced in BALB/c mice by ConA (25 mg/kg), and fucosterol (dissolved in 2% DMSO) was orally administered daily at doses of 25, 50, and 100 mg/kg. The levels of hepatic necrosis, apoptosis, and autophagy associated with inflammatory cytokines were measured at 2, 8, and 24 h. Results . Fucosterol attenuated serum liver enzyme levels and hepatic necrosis and apoptosis induced by TNF- α, IL-6, and IL-1 β . Fucosterol also inhibited apoptosis and autophagy by upregulating Bcl-2, which decreased levels of functional Bax and Beclin-1. Furthermore, reduced P38 MAPK and NF- κ B signaling were accompanied by PPAR γ activation. Conclusion . This study showed that fucosterol could alleviate acute liver injury induced by ConA by inhibiting P38 MAPK/PPAR γ /NF- κ B signaling. These findings highlight that fucosterol is a promising potential therapeutic agent for acute liver injury.